Preparation of Single Garlic, Red Ginger, Lemon and Apple Vinegar Combination Tablets By Wet Granulation Method - Wiendarlina, Ike Yulia; Fatmi, Mindiya; Indriati, Dwi; Novadin, Raraseta P (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2023)
Garlic, red ginger, lemon, and apple cider vinegar are spices in Indonesia that can be useful for increasing the body's resistance and preventing degenerative diseases. Tablet preparations are preferred because they are practical, easy to use, and easy to carry anywhere. The aim of this research is to see the effect of differences in the concentration of internal and external disintegrants, binders, gliders, and lubricants in each formula. Tablets are made with the single active ingredients of garlic, red ginger, apple cider vinegar, and lemon. The wet granulation method was chosen because natural materials have poor flow properties, so by using the wet granulation method, the flow rate, compressibility, and binding capacity of the granules can be improved for the better so that they can be molded into tablet preparations. The research results showed that all tablet formulas met the tablet evaluation requirements. The concentration of external and internal disintegrants, binders, gliders, and anti-adherents does not make a difference in flow time or angle of repose but provides different water content values in formula 3.There is an influence of differences in the concentration of additional ingredients on the quality of the tablets produced. The greater the concentration, the better the weight uniformity, the harder the resulting tablet, and the longer the disintegration time. Tablet fragility on F2 is high than formula 1 and 3, but still meets tablet quality requirements.